2019
DOI: 10.1097/ruq.0000000000000401
|View full text |Cite
|
Sign up to set email alerts
|

Can Presurgical Ultrasound Predict Survival in Women With Ovarian Masses?

Abstract: Purpose This study aimed to determine the ability of ultrasound to predict survival and detect more aggressive tumors in women with ovarian masses. Materials and methods Institutional review board approval was obtained. A total of 167 patients who presented with adnexal mass/masses were included. These were documented as benign or malignant on ultrasound. Age, date of diagnosis and date of death, type of tumor, and tumor marker cancer antigen 125 (CA-12… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…Given that some patients are unfortunately evaluated, either by dosing CA125 or by transvaginal ultrasound, it was found that patients who underwent ultrasound examination had suspected ovarian neoplasm had a much worse prognosis than those who had suspected disease based strictly on a modified CA125 [17][18][19][20][21][22].…”
Section: Transvaginal Ultrasoundmentioning
confidence: 99%
“…Given that some patients are unfortunately evaluated, either by dosing CA125 or by transvaginal ultrasound, it was found that patients who underwent ultrasound examination had suspected ovarian neoplasm had a much worse prognosis than those who had suspected disease based strictly on a modified CA125 [17][18][19][20][21][22].…”
Section: Transvaginal Ultrasoundmentioning
confidence: 99%